SYNTHESIS AND MAGNETIC CHARACTERIZATION OF [FE(ETA(5)-C9ME7)2]CENTER-DOT+[A]CENTER-DOT- (A = TCNE, TCNQ, DDQ) - X-RAY STRUCTURE OF [FE(ETA(5)-C9ME7)2]CENTER-DOT+[TCNQ]CENTER-DOT- - Murphy, V; Ohare, D (1994)
Addition of a solution of bis(η5-heptamethylindenyl)iron(II) to solutions containing polycyano acceptor molecules (TCNE (tetracyanoethylene), TCNQ (7,7,8,8-tetracyano-p-quinodimethane), or DDQ (2,3-dichloro-5,6-dicyanobenzoquinone)) results in the formation of 1:1 charge-transfer salts with the general composition [Fe(η-C9-Me7]2]•+[A] •- [A = TCNE, TCNQ, DDQ]. A single crystal X-ray structure determination has been performed for [Fe(η-C9Me7)2][TCNQ]. This compound belongs to the monoclinic centrosymmetric space group P21/n with a = 11.800(10) Å, b = 17.144(8) Å, c = 19.538(10) Å, β = 107.85(8)°, Z = 4, R = 0.063, Rw = 0.078. The solid-state structure consists of linear chains of D+A-D+A- alternating donor and acceptor ions. The cation adopts a partially eclipsed conformation with a rotation angle of 85° between the permethylindenyl rings. The iron C5-ring centroid distance is 1.717(8) Å with an average Fe-C distance of 2.108(8) Å. Solid-state magnetic susceptibility data for [Fe(η-C9Me7)2][TCNE] and [Fe(η-C9Me7)2][DDQ] in the temperature region 5-150 K can be modeled by the Curie-Weiss law (χmol = C/T - θ) with C = 0.96 and 0.53 (emu K)/mol and θ = -0.3(2) and -4(1) K, respectively. In contrast, the high-temperature magnetic susceptibility for [Fe(η-C9Me7)2][TCNQ] can be fitted to the Curie-Weiss law in the temperature region 10-100 K with C = 0.85 (emu K)/mol and θ = 6(1) K. At 2 K, the magnetization saturated at a rate faster than that predicted by the Brillouin function for two S = 1/2 independent spins; however, hysteresis effects were not observed. At 4 T, the magnetization saturates close to the expected value of 11 000 (emu G)/mol for two S = 1/2 units. In the temperature range 6-40 K, the magnetic susceptibility can be fitted to the isotropic 1-D Heisenberg model with a small ferromagnetic exchange parameter J = 5.0 K. The EPR spectrum of a single crystal of [Fe(η-C9Me7)2][TCNE], oriented with the needle axis of the crystal aligned perpendicular to the applied field, exhibits a single transition at g = 2.03, attributable to the g⊥ transition observed for the [Fe(η-C9Me7)•+ radical cation. The EPR spectrum of a frozen solution of [Fe(η-C9Me7)2][DDQ] exhibits an axially symmetric pattern with g∥ = 2.77 and g⊥ = 2.06, attributable to the [Fe(η-C9Me7)2]•+ radical cation. The lower g anisotropy (Δg = 0.71) compared to those reported for ferrocenium systems reflects the lower symmetry of the permethylindenyl ligand. © 1994 American Chemical Society.